Integration of Islamic Values in Islamic Education Learning Methods - Tarmizi Ninoersy; Nelli Isnayanti; Muhammad Alfithani Ninoersy (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
Islamic education emphasizes not only cognitive mastery but also aims to develop students' character and spiritual values holistically. In this context, integrating Islamic values into learning methods is a crucial strategy for achieving the holistic and integral goals of Islamic education. This paper theoretically examines how Islamic values can be internalized in various learning methods. Using a qualitative approach through literature review, it was found that learning methods in Islamic education must incorporate fundamental values such as monotheism, trustworthiness, sincerity, justice, and brotherhood. The value integration process is carried out through three main stages: learning planning that incorporates values as part of the learning outcomes; learning implementation that emphasizes exemplary and habituation approaches; and learning evaluation that considers students' affective and spiritual aspects. Methods such as reflective lectures, Islamic case studies, experiential learning, and teacher role models have been shown to support the process of internalizing values more effectively. The study results indicate that integrating Islamic values into learning can increase religious awareness, social ethics, and character development in accordance with Islamic teachings. Therefore, value integration is an important element in the development of Islamic education learning methods in the modern era